2018
DOI: 10.1002/cne.24480
|View full text |Cite
|
Sign up to set email alerts
|

A 3D MRI‐based atlas of a lizard brain

Abstract: Magnetic resonance imaging (MRI) is an established technique for neuroanatomical analysis, being particularly useful in the medical sciences. However, the application of MRI to evolutionary neuroscience is still in its infancy. Few magnetic resonance brain atlases exist outside the standard model organisms in neuroscience and no magnetic resonance atlas has been produced for any reptile brain. A detailed understanding of reptilian brain anatomy is necessary to elucidate the evolutionary origin of enigmatic bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 106 publications
3
30
0
3
Order By: Relevance
“…Squamates are becoming increasingly used as models in evolutionary and developmental neurobiology . However, the general difficulty of gross dissection of delicate, soft tissues like the embryonic brain is challenging, especially in small species; this task is facilitated by means of nondestructive imaging methods, such as magnetic resonance imaging (MRI) or diffusible iodine‐based contrast‐enhanced computed tomography (diceCT). Among amniotes, mammals and avian reptiles exhibit a well‐developed telencephalon that possesses derived internal architectures .…”
Section: Discussionmentioning
confidence: 99%
“…Squamates are becoming increasingly used as models in evolutionary and developmental neurobiology . However, the general difficulty of gross dissection of delicate, soft tissues like the embryonic brain is challenging, especially in small species; this task is facilitated by means of nondestructive imaging methods, such as magnetic resonance imaging (MRI) or diffusible iodine‐based contrast‐enhanced computed tomography (diceCT). Among amniotes, mammals and avian reptiles exhibit a well‐developed telencephalon that possesses derived internal architectures .…”
Section: Discussionmentioning
confidence: 99%
“…Corfield et al, 2008a; Berquist et al, 2012; Zeigler et al, 2014]. Recent studies have demonstrated the utility of MRI for comparative brain morphology in marine mammals [Marino et al, 2001a, b; Montie et al, 2008; Oelschlager et al, 2010; Berns et al, 2015], birds [Corfield et al, 2008a, b], reptiles [Hoops et al, 2014], teleosts [Van der Linden et al, 2004; Ullmann et al, 2010a, b, c] and cartilaginous fishes [Pradel et al, 2009; Yopak et al, 2009, 2010a; Yopak and Frank, 2007], which provides invaluable data on the size and precise anatomical position of major neuroanatomical features and allows for the non-invasive assessment of specimens. The majority of comparative neuroanatomical studies in non-mammalian vertebrates that utilize MRI have acquired 3D information for the purposes of assessment of whole brain volume or the volume of major brain regions across taxa [Marino et al, 2003; Kaufman et al, 2005; Oelschlager et al, 2008; Yopak and Frank, 2009; Ullmann et al, 2010c].…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate the applicability of STRP-seq for examining unconventional or rare samples we profiled brain sections from Pogona vitticeps, a non-model organism lizard endemic to semi-arid regions of Australia ( Fig. 4a,b; [33], [34]). We used STRP-seq to measure and reconstruct 8,183 annotated genes in the brain of P. vitticeps [35].…”
Section: Strp-seq Allows For the De Novo Reconstruction Of The Molecumentioning
confidence: 99%